Victory Gardeners: Food and Gardening as part of a Healthy Lifestyle and Community - Hunter, Maxine; Lester, William J.; Wooten, Hannah; Harlow, Erin E.; Silvasy, Tiare; Duncan, LuAnn; Elliott, Rebecca; DeForge, Samantha; Treadwell, Danielle (EDIS, 2023)
Healthy lifestyles, victory gardens, and Blue Zones are familiar terms to most, and each incorporates a holistic approach to human well-being. The therapeutic and nutritional benefits of gardening have long been recognized. After World War I, many service members were treated using horticulture therapy methods. During the early stages of the COVID-19 pandemic, many individuals and families turned to gardening as a source of supplemental food and physical and emotional wellness. The benefits of gardening, however, go beyond promoting physical health; they promote a healthful lifestyle. This is a holistic term which encompasses several dimensions of your life, including the spiritual, emotional, physical, intellectual, financial, social, and environmental dimensions (Lynch et al., 2021). This publication is a basic guide to incorporating gardening into your lifestyle including planning, planting, and harvesting considerations.